ADDRESSING VIEWS OF KEY INFORMANTS WHO ARE WORKING FOR WOMEN RIGHTS REGARDING INTIMATE PARTNER VIOLENCE - Nan Kyipyar Si (Belitung Nursing Journal, 2017)
Some married women are experiencing different types of intimate partner violence by their current or former husband. However, the awareness and services for those women are still needed. This study explored the key informants’ perspectives to provide more comprehensive services to those women. Qualitative feminist method was used and five participants were purposefully selected to interview in depth. Key informants reflected upon intimate partner violence as causes of intimate partner violence, why intimate partner violence cases were underreported, why didn’t women leave their violent partner, what they actually felt for intimate partner violence, gaps with intervention for survivors and planning for better outcome. It was found that awareness among women who experiencing violence and the people around them needed to be raised. And services provided for them also needed to be more concise and updated. Therefore, it is essentially important to extend education session to all people regarding violence against women. Collaboration and cooperation of government and non-governmental organizations is also helpful to decrease various kinds of violence committed to women.